SUBSTANTIATION OF THE COVERAGE WIDTH OF THE BODIES OF THE FRONTAL PLOW FOR FLAT PLOWING FOR CLASS 4 TRACTORS - Choriyeva Dilsabo Normamatovna (American Journals Publishing, 2025)
Substantiation of the coverage width of the bodies of the frontal plow for flat plowing for class 4 tractors.
Keywords: Resource-saving, frontal plow, combined, energy, open furrow, advanced technology, body, plug.